PENGEMBANGAN INSTRUMEN PENALARAN MATEMATIS UNTUK MENSTIMULASI KEMAMPUAN NUMERASI SISWA DENGAN KONTEKS “RUMAHKU” - Suriyani .; Mona Sri Wahyuni (Jurnal Education and Development, 2021)
The objectives of this study are: 1) To produce valid and effective mathematical reasoning instruments. 2) To determine students' numeracy abilities after being given mathematical reasoning instruments in the context of "my house". The population in this study were students of class VIII SMP N 3 Rantau Utara, amounting to 8 classes and the sample was taken 1 random class, namely class VIII-1. The design used in this study was the development (RnD). The research instrument used a description test and student response questionnaire sheets. The data were obtained from the results of a developed mathematical reasoning test given to students. From the results of data analysis, it was found that the results of the student numeracy ability test were: there were 5 students (16.6%) who had very good numeracy skills, 16 students (53.4%) had good numeracy skills, 5 students (16, 6%) have sufficient numeracy skills, and 4 students (13.3%) have low numeracy skills. So it has an average value of 66.8 in the good category. From the analysis of the test instrument effectiveness test using paired sample t-test, the correlation coefficient value is 0.161 with a significance value (Sig) of 0.000. Because the sig value is 0.000 <0.05, it can be concluded that there is a relationship between the initial and final variables. This means that the mathematical reasoning test development instrument is effective in stimulating students' numeracy skills.